Roald Dahl Little Library. 2, Creatures - Dahl, Roald; Blake, Quentin, 1932- (London : Puffin Books, 2019)
Learn whizzpopping creatures for all littlôe chiddlers from the world of Roald Dahl. A delightful treat for curious little hands, this little library is perfect for introducing titchy toddlers to new concepts, and to the imaginative world of Roald Dahl.
Part from the Roald Dahl Little Library (2 from 4) - Creatures
Keywords: leporelá; cudzojazyčná literatúra; čítame si spolu 0+